2012
DOI: 10.1242/jeb.069088
|View full text |Cite
|
Sign up to set email alerts
|

Feature-positive and feature-negative learning in honey bees

Abstract: SUMMARYHoney bees (Apis mellifera anatolica) were subjected to sequential trials where they were given the choice between a featurepositive and a feature-negative feeding plate. The ʻfeatureʼ being manipulated is the presence of a single blue circle among three circles marking the location of a small sucrose reward. That is, a ʻfeature-negativeʼ target had three white circles, while a ʻfeature-positiveʼ target had two white circles and one blue one. Two experiments were performed. In both experiments, each bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Between parts of an experiment, a new set of flowers was used (e.g. Wells and Wells 1986;Ç akmak et al 2009;Abramson et al 2013). These methods do not guarantee that flower odors have been eliminated completely from each artificial flower after being washed, because honey bees can perceive odors at concentrations\1 ppb.…”
Section: Methodsmentioning
confidence: 99%
“…Between parts of an experiment, a new set of flowers was used (e.g. Wells and Wells 1986;Ç akmak et al 2009;Abramson et al 2013). These methods do not guarantee that flower odors have been eliminated completely from each artificial flower after being washed, because honey bees can perceive odors at concentrations\1 ppb.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the single cue elicits anticipatory behavior, but animals withhold their responses when the same cue is presented in feature-negative trials. Studies have shown that the ability to conditionally discriminate between rewarded and unrewarded trials can occur in a wide range of species, from insects to humans (Pace et al, 1980;Nallan et al, 1981;Pace and McCoy, 1981;Abramson et al, 2013), and under a variety of stimulus conditions (Holland, 1997). In the mammalian brain there is evidence that these functions are mediated by specific circuits, including the retrosplenial cortex (Robinson et al, 2011), striatum, and orbitofrontal cortex (Meyer and Bucci, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates that while honey bees are able to learn through discrimination, they have difficulty with other types of problem solving (Abramson et al, 2008;Abramson et al, 2010;Abramson et al, 2013;Craig & Abramson, 2015). Abramson and colleagues (2008) found that bees were able to discriminate between two odors, which suggests that honey bees might be able to discriminate between positive and negative stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Bee success rates for the feature-negative trials were approximately 64% and approximately 60% for the feature-positive trials, which is a little better than chance (i.e., 50%). These findings suggest that the foragers did not retain information in detail from previous trials and that the bees had to reassess the problem during each trial (Abramson et al, 2013).…”
mentioning
confidence: 92%